Tourette’s Syndrome: Medical, Educational and Behavior Therapy - Dzeng, Annie; Wei, Mei-Hue (Journal of Behavior Therapy And Mental Health, 2015)
The French physician, Gill de la Tourette, was the first person to define Tourette’s Syndrome (TS) in 1885 and has brought much attention to it in Western countries for the past few decades. Unfortunately, most Asian countries are not familiar with Tourette’s Syndrome. Tourette’s Syndrome is regarded as a disorder of the nerve system that often appears with involuntary tic behaviors. The purpose of this article is to give a better understanding of Tourette’s Syndrome, starting with a brief background, followed by its pathogenesis and an analysis of treatment, including medication and education. The related studies of Tourette’s syndrome are also discussed in this study.
Keywords: Tourette’s Syndrome; comorbidities; treatments; behavior therapy.